The Evolution of Citizen Security in Colombia in Times of COVID-19 (2021)
This technical note examines the impact of the COVID-19 pandemic on crime and law enforcement dynamics in Colombia. The analysis uses administrative data on police reports and arrests for different types of offenses. It applies a “difference-in-differences” model, comparing the number of reports and arrests during the quarantine against their pre-quarantine trend. The results show a marked decline in homicides, motor vehicle theft, and other theft types in the initial weeks of the quarantine. The strong initial declines attenuated over time. The results reveal differences in crime dynamics between different regions of the country. The analysis also shows how COVID-19 modified police activity: arrests for offenses such as homicide and robbery decreased, and arrests due to threats to public health increased. This article contributes to a growing number of studies on the pandemic’s social impact and provides data and tools to inform citizen security and criminal justice policies.